The Revolutionary Movement of 1848-9 in Italy, Austria-Hungary, and Germany : With Some Examination of the Previous Thirty-three Years - Maurice, C. Edmund (Charles Edmund), 1843-1927 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Revolutionary Movement of 1848-9 in Italy, Austria-Hungary, and Germany" by C. Edmund Maurice is a historical account written in the late 19th century. The book explores the multifaceted revolutions that erupted across these regions during the tumultuous years of 1848 and 1849, detailing the interconnectedness of various national movements and historical contexts. It aims to present a comprehensive narrative that links individual uprisings and broader political phenomena across these nations, offering insights into the hopes and struggles for freedom and reform." "At the start of this historical account, the author lays the groundwork for understanding the vast socio-political landscape preceding the revolutions in Europe. It discusses the influence of previous decades of oppression and the rise of revolutionary fervor fueled by nationalistic aspirations. The preface hints at the connections between movements in different regions, highlighting figures such as Metternich and the distinct aspirations of different cultural groups within the empires involved. Maurice acknowledges the complexity of this revolutionary period, noting various socio-political dynamics that created a fertile ground for the uprisings that would soon follow." (This is an automatically generated summary.)
Release date is 2012-04-26
E-text prepared by Henry Flower, Odessa Paige Turner, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by the Google Books Library Project (http://books.google.com)
Keywords: Revolutions -- Europe; Europe -- History -- 1848-1849